The use of hypermedia in collaborative learning. An approach to the problem of complex systems in the teaching of urban planning / El uso de hipermedia en el aprendizaje colaborativo. Una aproximación al problema de los sistemas complejos en la docencia del urbanismo - Rosa-Jimenez, Carlos; Marquez-Ballesteros, Maria-José; Nebot, Nuria (Culture & Education / Cultura y Educación, 2018)
The counterpart to the open access to information facilitated by the Internet is the problem of the over-saturation of data and sources. A collaborative model of hypermedia is proposed as a pedagogical approach to the teaching of urban planning in which students organize and construct information from the possibilities provided by hypertext language. The methodology is structured in three phases: organization when searching for information; presentation of information using hypermedia; and assessment of the work. The results show that organization of information in the form of websites obtained the highest scores, although collaborative assessment should be restricted to subjective aspects of communication, while objective aspects should be assessed by the teacher and by groups of experts.